A Study on Green Entrepreneurship and Electronic Word of Mouth: Special Reference with Kanchipuram District - Rajalakshmi, A. R.; Jayakani, S.; Shanmugam, Harihara; Ramakrishnan, P. R. (Indian Journal of Information Sources and Services, 2024)
According to the literature, green products made in an environmentally friendly way are receiving more attention in the current context. Why are people so interested in these products, because of environmental interests such as conserving water, protecting natural resources, and health consciousness. Green entrepreneurs use this opportunity well. The current study tries to examine how electronic word of mouth influences green entrepreneurs and leads to green product purchasing associations, concurrently, Additionally, the study looks into the indirect link through the attitude towards environmental concern, environmental knowledge, and environmental consciousness. 235 customers participated in the survey as responders. In this study, women make up the majority of respondents. The respondents ranged in age from under 25 to over 55. To assess e-word-of-mouth influence, five indicators and to assess attitude towards environmental concern, environmental knowledge, and environmental consciousness eight indicators have been used. Frequency of Purchase of Green Products Respondents were asked to consider and provide specifics regarding the purchases of Green products in the previous months. The willingness to acquire Green goods is assessed by thinking about and specifying the possibility of purchasing Green products. An analysis indicates that e-word of mouth directly influences Green products which helps green entrepreneurs, and also indirectly through the attitude towards environmental concern, environmental knowledge, and environmental consciousness.